2019
DOI: 10.1159/000498920
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Depression in Relation to History of Childhood Trauma and Hair Cortisol Concentration in a Community-Based Sample

Abstract: Background: Childhood trauma represents a risk factor for developing depression with increased rates of recurrence. Mechanisms involved include a disturbed regulation of the hypothalamic–pituitary–adrenal (HPA) axis. Hair cortisol concentration (HCC) is a measure of long-term HPA axis activity with less interference from circadian and confounding factors. However, no study has so far used HCC to investigate the role of childhood trauma in recurrent pattern of depressive symptoms. Methods: A community-based sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
3
10
0
1
Order By: Relevance
“…Generally, studies investigating HCC in current MDD have had mixed results, with findings that HCC is higher [42, 43] than, or the same [44-46], or lower [47] as healthy controls. Some of these studies reported on the influence of various additional clinical variables.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Generally, studies investigating HCC in current MDD have had mixed results, with findings that HCC is higher [42, 43] than, or the same [44-46], or lower [47] as healthy controls. Some of these studies reported on the influence of various additional clinical variables.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Childhood maltreatment significantly impacts the proinflammatory immune state (Baumeister et al, 2016; Müller et al, 2019). In addition, childhood maltreatment seems to play a key role in HPA function and dysfunction in adulthood (Duncko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Spitzer et al (2018) determined that free salivary cortisol responses were not significantly different between women with or without major depression and with or without ELS history. Duncko et al (2019) found that within depressed patients, those with a history of ELS presented lower cortisol concentration when compared with those with no such history, although they have used hair cortisol, and not plasma cortisol, to assess it.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, early-life stress (ELS), such as childhood neglect; parental deprivation; lack of basic care; physical, sexual, and psychological violence (Heim et al, 2000;Cohen et al, 2001;Martins-Monteverde et al, 2019), have been shown as risk factors for depression in adulthood (Cohen et al, 2001;Heim and Nemeroff, 2001;Kendler et al, 2002). ELS can affect the clinical course and worsen the treatment outcome (Tunnard et al, 2014;Williams et al, 2016;Duncko et al, 2019) and can be related to disturbed development of brain structures during this neurodevelopmental window (Anisman et al, 1998;Andersen, 2003;Murmu et al, 2006;Lupien et al, 2009;Krugers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%